Genetic and developmental analysis of the locus vnd in Drosophila melanogaster. - White, K.; DeCelles, N.L.; Enlow, T.C. (Genetics, 1983)
Genetic and developmental analysis of an X-linked vital locus vnd was undertaken. Embryos hemizygous for the original allele vnd did not hatch and exhibited a disorganized ventral nervous system (VNS). The mutation maps in the region 1B6-7 to 1B9-10, a subregion of an area previously shown to be essential to normal neural development. In this paper, we report isolation of five new alleles at the locus vnd. Genetic complementation analysis of all mutations at the vnd locus, with lethal alleles at adjacent loci, indicates that all lesions at the locus vnd affect only one vital gene function in the region. Four of the five alleles are embryonic lethal; one allele is subvital and behaves like an hypomorphic mutation. Hemizygous embryos for three of the four embryonic lethal alleles were inspected in histological sections; all exhibited disorganized VNS similar to the original allele. The developmental analysis in gynandromorphic genetic mosaics shows that (1) vnd+ gene function is not essential in most imaginal-disc cell derivatives, (2) only about 30% of the mosaic zygotes survive as adults, (3) mosaic zygotes with mutant tissue close to the head cuticle are least likely to survive, and (4) mutant tissue in the thoracic ganglion in the adult is not necessarily lethal. The mosaic data are consistent with the vnd+ gene function being necessary in neural cells derived from the anterioventral region of the blastoderm.